Modeling of contact interaction and wear of the trolleybus contact insert-wire tribopair - Holenko, K.E.; Kovtun, O.S; Dykha, O.V. (Проблеми трибології, 2025)
The article presents the results of numerical modeling of the contact interaction of the tribopair "contact insert - contact wire" of a trolleybus using the Ansys software environment. The main attention is paid to the analysis of the stress state and the prediction of wear of friction surfaces when modeling a stable frictional contact. Based on the constructed solid-state models of the contact insert and the MF-100 copper wire, a finite element mesh was formed and real conditions of operational loading were simulated. The distributions of contact pressure, frictional and equivalent stresses, as well as the nature of the contact spot were determined. Linear wear was calculated using the energy criterion, taking into account local frictional stresses and material hardness. The obtained results were compared with the available experimental data, which confirms the adequacy of the proposed model. The article also outlines the prospects for interpolation of short-term simulations into long-term operating modes by mathematical modeling of wear under variable load. The material is useful for predicting the service life of current collection devices and optimizing their geometry and materials